2012
DOI: 10.1521/pedi.2012.26.3.428
|View full text |Cite
|
Sign up to set email alerts
|

Peer Victimization as a Risk Factor for Schizotypal Personality in Childhood and Adolescence

Abstract: There has been no prior research on peer victimization and child or adolescent schizotypal personality. This study tests the hypothesis that increased peer victimization is associated with increased schizotypal personality. Schizotypy was assessed using the SPQ-C (Schizotypal Personality Questionnaire-Child) in 3,508 male and female schoolchildren aged 8 to 16 years. All forms of peer victimization (physical, verbal, social manipulation, attack on property) were associated with schizotypal personality in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
3
8
0
1
Order By: Relevance
“…These victimization experiences would then, in turn, promote a retaliatory reactive aggression. Their proposal is consistent with other studies that have found victimization to be positively related to both schizophrenia and reactive aggression independently (Fung and Raine, 2012;Poulin and Boivin, 2000).…”
Section: Aggression and Schizotypysupporting
confidence: 92%
“…These victimization experiences would then, in turn, promote a retaliatory reactive aggression. Their proposal is consistent with other studies that have found victimization to be positively related to both schizophrenia and reactive aggression independently (Fung and Raine, 2012;Poulin and Boivin, 2000).…”
Section: Aggression and Schizotypysupporting
confidence: 92%
“…Similar to findings in schizophrenia, prenatal insults, such as influenza exposure during the 6th month of gestation (specifically, week 23) have been associated with higher scores of schizotypal traits in an adult male population [11]. A number of forms of psychological trauma [12;13] and chronic stress [14] have been associated with SPD. The effect of trauma on the development of schizotypal symptoms, however, appears to be dependent on genetic background.…”
Section: Pathogenesis Of Spdmentioning
confidence: 76%
“…Environmental stressors can exacerbate these traits in vulnerable individuals. For instance, in one study, peer victimization predisposed individuals to paranoid ideation and heightened schizotypal personality among 3,508 children and adolescents (5). Moreover, college students with schizotypal personality tend to experience higher levels of paranoid ideation and general health problems (6).…”
Section: Introductionmentioning
confidence: 99%